On the flow of a thin liquid layer in an inclined channel of triangular transverse section driven by a surface tension gradient. Numerical and asymptotic analysis - Petrila, Titus; Borşa, Emilia (Rev. Anal. Numér. Théor. Approx., 2003)
In this paper we investigate the locally unidirectional flow of a thin liquid layer confined to an inclined channel driven simultaneously by a surface tension gradient.